THE LEVELS OF QUESTIONS USED ON READING TEST WITH REGARDS TO REVISED BLOOM'S TAXONOMY - Yenni Kurnia Fitri; Hermawati Syarif; Desvalini Anwar (Ta'dib, 2019)
The research aims to find out the levels of questions used by an English teacher for mid-semester reading test for the second graders in SMA 2 Padang in accordance Anderson’s and Karthwohl’s taxonomy (2001). The participant was chosen based on purposive sampling. This is a descriptive research. The data of the research were obtained from documents analysis. Evaluation of the question sheets were analyzed one by one. After that, the data were analyzed, grouped, and explained based on the research aims. The results of this research show that the teacher formulated on three levels of questions. They are the questions remembering (46.67%), understanding (36.66%), and applying (16.67%). From the result, it can be concluded almost half of the questions are in the form of remembering and least of them for applying.